2022
DOI: 10.48550/arxiv.2202.04118
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure formation in mimetic gravity

Abstract: Mimetic theory of gravity was proposed as an alternative description for the dark matter (DM) puzzle. It was argued that the mimetic field can encode a dynamical longitudinal degree of freedom which can play the role of mimetic DM. In this paper, we disclose the effects of an extra longitudinal degree of freedom on the evolution of perturbations in the framework of mimetic gravity. We consider a flat Friedmann-Robertson-Walker (FRW) background and explore the linear perturbations by adopting the spherically sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 70 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…Moreover, mimetic theory can investigate the flat rotation curves of spiral galaxies without the need of dark matter [14,15]. From a cosmological point of view, the theory of mimetic has discussed a lot of interesting research papers in the past few years [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and black holes physics [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]. It has been shown that for a spherically symmetric spacetime the only solution is the Schwarzschild spacetime which means that the Birkhoff's theorem is hold.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, mimetic theory can investigate the flat rotation curves of spiral galaxies without the need of dark matter [14,15]. From a cosmological point of view, the theory of mimetic has discussed a lot of interesting research papers in the past few years [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and black holes physics [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]. It has been shown that for a spherically symmetric spacetime the only solution is the Schwarzschild spacetime which means that the Birkhoff's theorem is hold.…”
Section: Introductionmentioning
confidence: 99%
“…An appropriate approach to investigate the growth of perturbations and structure formation is the so called Top-Hat Spherical Collapse (SC) model [3]. In this approach one considers a uniform and spherical symmetric perturbation in an expanding background and describes the growth of perturbations in a spherical region using the same Friedmann equations for the underlying theory of gravity [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…An appropriate approach for investigating the growth of perturbations and structure formation is the so-called top-hat spherical collapse (SC) model [3]. In this approach, one considers a uniform and spherically symmetric perturbation in an expanding background and describes the growth of perturbations in a spherical region using the same Friedmann equations for the underlying theory of gravity [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%